Hubungan Antara Persepsi Perilaku Merokok Dengan Perilaku Merokok Siswa SMK X Di Kota Semarang - Febriana Rahayuningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Based on the data, Student of SMK X in Semarang who smoked at 85,6%. The purpose of this study to analyze the relationship between the perception of smoking behavior and smoking behavior student of SMK X in Semarang. The method used quantitative cross-sectional approach. The population is an active student of SMK X in Semarang with a total of 1,206 people and as many as 104 samples were taken using a random sampling method with random sampling technique propportional sampling. Source of research data using primary data and secondary data. Analysis of data using univariate and bivariate analysis with Chi Square test (significance level 0.05). Most of the respondents were 17-20 years of age (late teens) (51.9%), most of the respondents' gender is male at 92.3% and the grade level of the respondents were in grade 10 (36.5%). Work parent respondents was (50.0%) were self-employed and the amount (41.3%) had a family member smoker responen by 1 person. Respondents had the experience of smoking at (59.6%), knowledge of respondents in both categories (73.1%), perceived susceptibility (55.8%), perceived seriousness (74%), perceived benefits (69.2%) and perceived barriers (74%). Chi Square test results found there is relationship between gender, occupation of parents, the number of smokers family, experience, knowledge, and perceived benefits. As for age, grade level, perceived susceptibility, perceived seriousness, perceived barrier no relation with smoking practices student of SMK X. So that the results of these studies, the need for a commitment or regulations prohibited smoking in school and confirmed with strict sanctions and penalties. In addition, health socialization is also required about the dangers of smoking, then supervision of the family also needs to be improved.